Meningkatkan Kreativitas Siswa SD Dalam Model Pembelajaran Problem Based Learning - Dwi Nursanti Nursanti; Muhammad Muslih; Aini Munawaroh Nurd; Nur Ngazizah (Indonesian Publication Center, 2022)
Creative thinking skills are useful in improving process skills and learning outcomes in the learning process. The researcher conducted an interview with Mrs. Hanik Nihadayatul Muslimah S.Pd (Class IV Teacher) SD N Roworejo. Based on the results of the study, the researchers came to a conclusion and gave suggestions to teachers on how to increase creativity and student learning outcomes. Problem-based learning model (PBL) is a student-centered learning model for students who are faced with various problems. faced in real life. Through PBL mode, students not only listen, record and memorize the material given by the teacher, but also think, search, process data and communicate in the learning process. This research is the result of observations made by researchers directly on March 29, 2022 at SD N Roworejo, Grabag District, Purworejo Regency. Researchers collected data through relevant sources, namely Mrs. Hanik Nihayatul Muslimah S.Pd as a fourth grade teacher. The data analysis technique used descriptive qualitative data analysis. Based on the observations of 17 students, there were 5 students or 29% with an average score of 52 under 70 KKM. The results of data analysis showed that 11 students with a percentage of 64% completed or achieved scores above the KKM.